Theological and Sociological Accounts of a Buddhist Meditation Practice: illusory bodies - Mullen, Kenneth (Journal of beliefs and values, 1999)
Techniques of mental visualisation, and the visualisation of the body of the Buddha in particular, are central to many Buddhist meditation practices. The article begins with a description of a Tibetan meditation centred on the visualisation of the Bodhisattva of Compassion. This is followed by two accounts of the meaning of this practice: first as elucidated within the Buddhist theological/philosophical framework, and second, from a sociological standpoint. Core elements of the Buddhist philosophy of the body underpinning this practice are elucidated: ideas relating to the provisional nature of reality, interdependence and the central concept of the mutability of the self. Recent theorising within the sociology of the body views the self as being charged with emotions, discusses body image, and aims to deconstruct our notions of materiality. The article draws out the similarities between aspects of Buddhist theology/philosophy and current sociological thinking about the body.